Connections between job satisfaction and depression, anxiety, and stress among nurses - Agnė Buivydienė; Lolita Rapolienė; Marija Truš; Agnė Jakavonytė-Akstinienė (Frontiers in Psychology)
IntroductionAs a cornerstone of overall wellbeing, mental health significantly influences job satisfaction, vital for employee retention and organizational success. Recognizing this, managers prioritize initiatives to enhance job satisfaction and promote a healthy, productive work environment.AimsThe study aims to explore the connections between depression, anxiety, stress, and job satisfaction among nurses, providing insights to improve their wellbeing and retention in the profession.MethodsThis quantitative survey study was conducted from June to September 2024, involving 643 nurses from healthcare facilities in Klaipėda County. Data were collected using two validated instruments: the Depression, Anxiety Stress Scales (DASS-42) and the Paul Spector Job Satisfaction Survey (JSS). Statistical analysis was performed using IBM SPSS Statistics Version 29.0.1.0.ResultsThe study found that while the average levels of depression, anxiety, and stress among nurses were within normal limits, a significant portion of participants exhibited compromised mental health. Nearly one-third of the nurses experienced stress and/or depression, and almost half reported anxiety. Over one-sixth of the participants experienced high or very high levels of anxiety, while severe depression or stress was less common. Factors such as years of experience, workload, and work schedule were identified as significant influences on nurses’ psychoemotional state. Moderate to strong positive correlations were observed between depression, anxiety, and stress levels. Additionally, the nurses’ mental health was statistically significantly and negatively associated with most components of job satisfaction.ConclusionDespite average levels of depression, anxiety, and stress being within normal limits, many nurses face significant mental health challenges, particularly anxiety. Factors like workload and work schedules strongly influence their wellbeing. The negative link between mental health and job satisfaction highlights the need for better support to improve nurses’ wellbeing and job satisfaction.